1998
DOI: 10.1097/00007632-199808010-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematic Study of the Cervical Spine Before and After Segmental Arthrodesis

Abstract: Under what was considered a realistic loading paradigm, sagittal plane rotation was not increased disproportionately at the motion segments immediately adjacent to a segmental arthrodesis in the cervical spine. The nonlinear rise in applied bending moment to achieve constant displacement was characteristic of the behavior of the ligaments and intervertebral discs throughout the spine as they underwent increasing deformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 14 publications
2
67
1
2
Order By: Relevance
“…However, studies on cervical fusion have reported an increased adjacent-level intradiscal pressure and range of motion [1][2][3][4]. The procedure has thus been perceived to accelerate adjacent segment degeneration (ASD) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on cervical fusion have reported an increased adjacent-level intradiscal pressure and range of motion [1][2][3][4]. The procedure has thus been perceived to accelerate adjacent segment degeneration (ASD) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the evidence suggesting an increased range of motion and disc pressure [16,20] in the segment adjacent to the fused one, the replacement of the degenerate disc with a disc prosthesis, to avoid immobilisation of the spinal segment, seemed to be a logical concept. In the lumbar spine, disc replacement has been in existence for more than 25 years [48], but the implant never achieved the popularity that was initially anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of late adjacent-level degenerative changes, such as anterior osteophyte formation or ossification of the anterior longitudinal ligament, has been reported following anterior cervical arthrodesis [5][6][7][8][9][10][11] . Furthermore, there have been few studies concerning the association of anterior cervical plates and late degenerative changes.…”
Section: Discussionmentioning
confidence: 99%